Clinical characteristics and outcome of surgical treatment of childhood rhabdomyosarcoma: A 7-year experience - Uba Francis; Chirdan Lohfa (Wolters Kluwer Medknow Publications, 2008)
Background: The aim of this study was to describe the outcome and determine the prognostic factors of outcome of childhood rhabdomyosarcoma in a tertiary hospital in a developing country. Patients and Methods: This was a retrospective review of the clinical presentation, investigation, intervention, and treatment outcomes of children with rhabdomyosarcoma in our hospital over a 7-year period. Statistical analysis was performed using Chi-square test. Results: A total of 18 patients were identified with two-thirds being males (n = 12) with median age of 7 years. Most of the children were below 10 years of age. Lower limbs tumour predominated (n = 6) followed by the upper limbs and head and neck (n = 4 each). Other sites included perianal/perineal (n = 3) and the orbit (n = 1). Two patients were Intergroup Rabdomyosarcoma Study (IRS) group I, four group II, five group III, and seven group IV. Lymph node involvement was the commonest site of metastasis. Clinical group and stage was significantly more advanced in patients older than 10 years compared to younger than 10 years (P = 0.010, P = 0.008, respectively). There were 12 patients with alveolar disease while six had embryonal type of rhabdomyosarcoma. Treatment was by combination chemotherapy, and surgical excision which was done primarily in 11, after chemotherapy in four, and after radiotherapy in one. Two had biopsy only. Five patients are alive, two of them without evidence of disease at average follow-up period of 2 years. Conclusion: Mortality from rhadomyosarcoma in our setting is still unacceptably high. Late presentation may be the major contributor to high mortality. A more aggressive multimodality treatment approach may improve the outcome.